Implementation of pseudo-dynamic mode of working standards of gas volume - Kuz, M. V. (Visnyk of Vinnytsia Politechnical Institute, 2013)
Modernisation of working standards working in the discretely-dynamic mode is offerd, by develop-ment of device of indemnification of pneumo-impacts. Introduction of such device to the construction of working standards provides the pseudo-dynamic mode of operations of the working standard. Due to the offered modernisation making the of reproducing errors of gas volume from influence of pressure fluctuation is diminished from 0,27 % to 0,08 %.